Cartographic and analytical assessment of land price formation depending on the physical and geographical conditions of the territory under military aggression in Ukraine - Петро Трофименко; Анна Мінженер; Віталій Зацерковний; Ірина Стахів; Світлана Кобилянська (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Background. The presented study sheds light on the issue of land price formation in Ukraine as a result of military aggression in conditions of uncertainty. The research involved identifying the peculiarities of the formation of the real price of land plots in the case of concluding a purchase and sale agreement in conditions of uncertainty, depending on a complex of price-forming factors, primarily, taking into account the distance from the line of combat with intensive combat operations, geographical conditions of the territory. It has been shown that the land market under wartime conditions is effectively in a state of stagnation due to numerous risks for both sellers and buyers. The lack of clear legal regulation and the high risk of property loss lead to land purchase and sale transactions being carried out with significant restrictions, which do not meet the criteria for the full functioning of a market mechanism.